Letrozole targets the human ether‐a‐go‐go–related gene potassium current in glioblastoma. Issue 3 (27th October 2020) - Shugg, Tyler; Dave, Nimita; Amarh, Enoch; Assiri, Abdullah A.; Pollok, Karen E.; Overholser, Brian R.
Abstract: Aberrant expression of human ether‐a‐go‐go–related gene (hERG) potassium channels has been implicated in the pathophysiology of glioblastoma (GBM). Letrozole has demonstrated efficacy in pre‐clinical GBM models. The objective of this research was to assess the potential for hERG inhibition by letrozole to mediate efficacy in GBM. hERG currents were assessed using patch‐clamp electrophysiology in an overexpression system during treatment with letrozole, exemestane or vehicle (dimethyl sulphoxide). Relative to vehicle, peak hERG tail current density was reduced when treated with 300 nmol/L and 1 µmol/L letrozole but not when treated with exemestane (up to 1 µmol/L). Cell proliferation was assessed in cultured glioblastoma cell lines (U87 and U373) treated with letrozole, exemestane, doxazosin (hERG blocker) or vehicle. Letrozole, but not exemestane, reduced cell proliferation relative to vehicle in U87 and U373 cells. The associations between expression of hERG (KCNH2), aromatase (CYP19A1) and the oestrogen receptors (ESR1 and ESR2) and time to all‐cause mortality were assessed in GBM patients within The Cancer Genome Atlas (TCGA) database. hERG expression was associated with reduced overall survival in the TCGA GBM cohort. Future work is warranted to investigate hERG expression as a potential biomarker to predict the therapeutic potential of hERG inhibitors in GBM.